Contribution of Individual Risk Factor Changes to Reductions in Population Absolute Cardiovascular Risk. (5th June 2014) - Cochrane, Thomas; Davey, Rachel; Gidlow, Christopher; Iqbal, Zafar; Kumar, Jagdish; Mawby, Yvonne; Chambers, Ruth
Abstract : Background . Few studies have investigated individual risk factor contributions to absolute cardiovascular disease (CVD) risk. Even fewer have examined changes in individual risk factors as components of overall modifiable risk change following a CVD prevention intervention. Design . Longitudinal study of population CVD risk factor changes following a health screening and enhanced support programme. Methods . The contribution of individual risk factors to the estimated absolute CVD risk in a population of high risk patients identified from general practice records was evaluated. Further, the proportion of the modifiable risk attributable to each factor that was removed following one year of enhanced support was estimated. Results . Mean age of patients (533 males, 68 females) was 63.7 (6.4) years. High cholesterol (57%) was most prevalent, followed by smoking (53%) and high blood pressure (26%). Smoking (57%) made the greatest contribution to the modifiable population CVD risk, followed by raised blood pressure (26%) and raised cholesterol (17%). After one year of enhanced support, the modifiable population risk attributed to smoking (56%), high blood pressure (68%), and high cholesterol (53%) was removed. Conclusion . Approximately 59% of the modifiable risk attributable to the combination of high blood pressure, high cholesterol, and current smoking was removed after intervention.